2016
DOI: 10.1016/j.cub.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

An Ectopic Network of Transcription Factors Regulated by Hippo Signaling Drives Growth and Invasion of a Malignant Tumor Model

Abstract: Cancer cells have abnormal gene expression profiles; however, to what degree these are chaotic or driven by structured gene regulatory networks is often not known. Here we studied a model of Ras-driven invasive tumorigenesis in Drosophila epithelial tissues and combined in vivo genetics with next-generation sequencing and computational modeling to decipher the regulatory logic of tumor cells. Surprisingly, we discovered that the bulk of the tumor-specific gene expression is controlled by an ectopic network of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
110
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 49 publications
11
110
0
Order By: Relevance
“…Besides, a latest study shows CCNE2 is involved in regulation of Hippo pathway in breast cancer (Pegoraro et al, 2015). Hippo pathway is characterized as a tumor-suppressive axis, and plays important roles in tumor cellular process including proliferation, migration, invasion, and apoptosis (Alam et al, 2016; Atkins et al, 2016; Kemppainen et al, 2016; Mao et al, 2016). YAP is an important transcriptional activator and can be phosphorylated by Hippo pathway (Bouvier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a latest study shows CCNE2 is involved in regulation of Hippo pathway in breast cancer (Pegoraro et al, 2015). Hippo pathway is characterized as a tumor-suppressive axis, and plays important roles in tumor cellular process including proliferation, migration, invasion, and apoptosis (Alam et al, 2016; Atkins et al, 2016; Kemppainen et al, 2016; Mao et al, 2016). YAP is an important transcriptional activator and can be phosphorylated by Hippo pathway (Bouvier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In our work, abrupt expression levels were up-regulated in eye discs where there was forced maintenance of hth or hth + tsh (with a fold change of approximately 2 in both situations), suggesting also a role in the control of the expression of nuclear receptors in progenitors. More recently, overexpression of taiman and ftz - f1 was also shown to be present in a model of invasive cancer driven by RAS in the eye disc 68 . In the cancer models mentioned above, a role for the Hippo pathway has been described 66, 68 .…”
Section: Discussionmentioning
confidence: 95%
“…More recently, overexpression of taiman and ftz - f1 was also shown to be present in a model of invasive cancer driven by RAS in the eye disc 68 . In the cancer models mentioned above, a role for the Hippo pathway has been described 66, 68 . Therefore, a similar nuclear receptor (and probably abrupt ) expression pattern might be a general feature of Hippo-related tissue overgrowth.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, blocking JNK signaling by over‐expressing the JNK phosphatase Puckered (Puc) significantly suppressed cell death at the nubbin/non‐nubbin boundary (Figure a, quantified in Figure e). It has been reported that cells with higher expression of dMyc, a crucial regulator of cell growth and cell cycle progression, outcompete surrounding cells with lower dMyc expression by supercompetition (de la Cova, Abril, Bellosta, Gallant, & Johnston, ; Moreno & Basler, ), and that over‐expression of dMyc suppresses cell competition triggered by cell polarity defect (Atkins et al., ). Intriguingly, however, over‐expression of dMyc in RpS3‐RNAi ‐expressing nubbin cells did not suppress cell death at the nubbin/non‐nubbin boundary (Figure b, quantified in Figure e).…”
Section: Resultsmentioning
confidence: 99%